The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1101/2020.01.19.911313
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Potential short-term earthquake forecasting by farm-animal monitoring

Abstract: Whether changes in animal behavior allow for short-term earthquake predictions has been debated for a long time. During the 2016/2017 earthquake sequence in Italy, we instrumentally observed the activity of farm animals (cows, dogs, sheep) close to the epicenter of the devastating magnitude M6.6 Norcia earthquake (Oct-Nov 2016) and over a subsequent longer observation period (Jan-Apr 2017). Relating 5304 (in 2016) and 12948 (in 2017) earthquakes with a wide magnitude range (0.4 ≤ M ≤ 6.6) to continuously measu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…Via randomization of the animal anomalies, they demonstrate the low significance of the relationship found in our analysis. We agree with this result, which we already discuss in the paper and in detail in the significance patterns in the supplementary materials (Wikelski et al, 2020). As we cannot control other external factors affecting animal activity with the data at hand, a low significance of the relationship is not surprising.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Via randomization of the animal anomalies, they demonstrate the low significance of the relationship found in our analysis. We agree with this result, which we already discuss in the paper and in detail in the significance patterns in the supplementary materials (Wikelski et al, 2020). As we cannot control other external factors affecting animal activity with the data at hand, a low significance of the relationship is not surprising.…”
supporting
confidence: 92%
“…Zöller et al (2020) somewhat misinterpret the goal of our paper (Wikelski et al., 2020), which neither tries to perform earthquake predictions nor does it claim that the current quality of measurements is sufficient to perform earthquake predictions.…”
mentioning
confidence: 82%
“…Using animal sentinels as a lens to the environment is in itself not new, as they have long been employed to detect human exposure to biological and chemical hazards (e.g., canaries in coal mines) 27,28 . Moreover, anecdotal evidence has linked animal behavior to the onset of natural disasters 29,30 , and recent evidence suggests that dogs can be used to provide an early warning of epileptic seizures 31 or outbursts of violence 32 . Elucidating the hitherto hidden information in the behavior of animals with cutting-edge technology can help us gauge the conditions of life on Earth 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Data and python code have been downloaded from the Supplementary Material of Wikelski et al. (2020).…”
Section: Data and Resourcesmentioning
confidence: 99%
“…Here, we apply this technique in order to study whether or not the anticipatory patterns between animal and seismic activity reported by Wikelski et al. (2020) (hereinafter referred to as WK2020) have significant forecasting skills. We restrict our analysis to a statistical evaluation of the forecasting power and refrain from commenting on the plausibility of such patterns or on the modeling technique used to generate the proposed precursor.…”
Section: Introductionmentioning
confidence: 99%